HUBUNGAN ANTARA TEKANAN DARAH DIASTOLE IBU DENGAN BERAT BADAN LAHIR BAYI PADA IBU YANG MELAHIRKAN DENGAN UMUR KEHAMILAN ATERM DI WILAYAH KERJA PUSKESMAS KUBUTAMBAHAN II BULELENG - Ni Putu Neysa Putri Arthayani; Ni Gusti Kompiang Sriasih; Listina Ade Widya Ningtyas (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2023)
As much as 60–80% of the infant mortality rate that occurs is caused by low birth weight. This study aims to determine the relationship between diastolic blood pressure and birth weight at the Kubutambahan II Community Health Center, Buleleng. This research is an analytical research with a cross sectional approach. The research was carried out in February – March 2022. The population of this research study were all newborn babies in the work area of the Kubutambahan II Health Center. The research sample used was 55 respondents. The results of the univariate analysis showed that 81.8% of mothers had normal blood pressure, and 76.4% of babies had normal birth weight. The results of the bivariate test showed that there was a relationship between diastolic blood pressure and birth weight, with a value of p = 0.003. The OR value was 8.143 (95% CI: 1.817-36.500). The conclusion of this study, 55 respondents showed a significant relationship between maternal diastolic blood pressure and the baby's birth weight. The results of the research hope that health workers will be more careful in detecting early the signs and dangers of pregnancy, especially hypertension.